Analysis of Catcalling on Mental Health of Female Students in Elementary Schools - Laila, Nabilla Nurul (International Journal of Students Education, 2024)
Catcalling, as a form of verbal harassment, has become an increasingly concerning issue in educational settings, especially for female students in primary schools. This experience can have negative impacts on their mental health, including anxiety, discomfort in social interactions, and decreased self-esteem. This study used a literature review approach by analyzing various relevant journal sources regarding catcalling and its impact on girls’ mental health. Data were collected from 10 studies covering international and national perspectives. The analysis showed that catcalling contributes to increased levels of anxiety and social discomfort among female students. In addition, many studies have found that catcalling can damage self-image and lower self-confidence, creating an unsafe environment for them. Catcalling not only affects current mental health, but can also have long-term impacts on the social and emotional development of female students. With increased fear and low self-esteem, girls who experience catcalling tend to avoid social interactions, which in turn can hinder their development in the school environment. This study emphasizes the importance of creating a safe and supportive educational environment for all students, as well as the need for educational programs to prevent catcalling and support girls’ mental health. Collaborative efforts from various parties are expected to reduce the negative impacts of catcalling and improve the quality of children’s learning experiences.